PKPD modelling of the interrelationship between mean arterial BP, cardiac output and total peripheral resistance in conscious rats. (12th July 2013) - Snelder, N; Ploeger, B A; Luttringer, O; Rigel, D F; Webb, R L; Feldman, D; Fu, F; Beil, M; Jin, L; Stanski, D R; Danhof, M
Abstract : Background and Purpose: The homeostatic control of arterial BP is well understood with changes in BP resulting from changes in cardiac output (CO) and/or total peripheral resistance (TPR). A mechanism‐based and quantitative analysis of drug effects on this interrelationship could provide a basis for the prediction of drug effects on BP. Hence, we aimed to develop a mechanism‐based pharmacokinetic‐pharmacodynamic (PKPD) model in rats that could be used to characterize the effects of cardiovascular drugs with different mechanisms of action (MoA) on the interrelationship between BP, CO and TPR. Experimental Approach: The cardiovascular effects of six drugs with diverse MoA, (amlodipine, fasudil, enalapril, propranolol, hydrochlorothiazide and prazosin) were characterized in spontaneously hypertensive rats. The rats were chronically instrumented with ascending aortic flow probes and/or aortic catheters/radiotransmitters for continuous recording of CO and/or BP. Data were analysed in conjunction with independent information on the time course of drug concentration using a mechanism‐based PKPD modelling approach. Key Results: By simultaneous analysis of the effects of six different compounds, the dynamics of the interrelationship between BP, CO and TPR were quantified. System‐specific parameters could be distinguished from drug‐specific parameters indicating that the model developed is drug‐independent. Conclusions and Implications: A system‐specific model characterizing the interrelationship between BP, CO and TPR was obtained, which can be used to quantify and predict the cardiovascular effects of a drug and to elucidate the MoA for novel compounds. Ultimately, the proposed PKPD model could be used to predict the effects of a particular drug on BP in humans based on preclinical data.